Effect of carbohydrate type on small dense low-density lipoprotein levels in patients with coronary heart disease: a randomized controlled trial - Nofia, Vino Rika; Angraini , Siska Sakti; Herlina , Andika; Dewi , Ratna Indah Sari; Ibrahim, Ibrahim; Yusuf , Rahmi Novita (Universitas Muhammadiyah Purwokerto, 2026)
Background: Coronary heart disease (CHD) is closely associated with dyslipidemia, particularly elevated small dense low-density lipoprotein (sdLDL), which contributes to increased atherogenic risk. Evidence from controlled dietary interventions examining the impact of carbohydrate type on sdLDL levels among patients with coronary heart disease in Indonesia remains limited. Objective: This study aimed to evaluate the effect of simple versus complex carbohydrate intake on lipid profiles, with a primary focus on sdLDL levels, in patients with CHD. Methods: A pretest–posttest single-blind randomized controlled trial was conducted among 40 clinically stable patients with coronary heart disease at a community health center in Padang City, Indonesia. Participants were randomly assigned to consume either refined white rice (simple carbohydrate) or unrefined brown rice (complex carbohydrate) for four weeks. Lipid profiles were assessed at baseline and post-intervention. Results: The complex carbohydrate group demonstrated a significantly greater reduction in sdLDL levels compared with the simple carbohydrate group. Significant improvements in total cholesterol, LDL cholesterol, and HDL cholesterol were also observed in the complex carbohydrate group, while triglyceride levels did not change significantly in either group. Conclusion: Complex carbohydrate intake resulted in more favorable modulation of atherogenic lipid profiles than simple carbohydrate intake in patients with coronary heart disease. These findings highlight the importance of carbohydrate quality, particularly unrefined rice-based staples, as a complementary dietary strategy in CHD management.